Lecture 07
Lecture 07
LCCDE
The Discrete-Time Fourier Transform (DTFT) of a signal x(n) is
defined by:
X
j
x(n)e jn
X (e ) =
n=
CHUM Pharino
November 6, 2016
This material is property of author and is for sole and exclusive use of his students. It is not for publication, nor it is to be sold,
reproduced, or generally distributed.
lecture #06
November 6, 2016
1 / 23
Application of DTFT I
lecture #06
November 6, 2016
2 / 23
Application of DTFT II
Inverse System: Using Fourier Transforms, it is easy to find inverse
system for signal reconstruction problems, when they exist.
Example: The frequency response if a system is
H(e e ) =
1 + 0.25e j
1 0.5e j
h(n) = an u(n)
y (n) = (n)
Solution:
G (e j ) = H 1 (e j ) =
1 0.5e j
1 + 0.25e j
There are some serious practical issues with this solution. Can you
think of some?
The author (ITC)
lecture #06
November 6, 2016
3 / 23
lecture #06
November 6, 2016
4 / 23
Application of DTFT IV
Rewriting, we have
(
)
(M
)
N
X
X
j
j jk
j
j jk
Y (e ) 1
a(k)Y (e )e
= X (e )
b(k)X (e )e
N
X
a(k)y (n k) +
k=1
M
X
k=1
b(k)x(n k)
y (n) =
k=0
k=0
N
X
a(k)y (n k) +
k=1
b(k)x(n k)
k0
Solution
y (n) = F 1 Y (e j )
where
Y (e j ) =
M
X
N
X
a(k)Y (e j )e jk +
k=1
M
X
PN
jk
k=0 b(k)e
P
X (e j )
n
1 k=1 a(k)e jk
b(k)X (e j )e jk
k=0
lecture #06
November 6, 2016
5 / 23
N
X
lecture #06
November 6, 2016
6 / 23
Example
a(k)y (n k) +
k=1
M
X
b(k)x(n k)
k0
H(e j ) =
1 1.4142e j + e 2j
1 1.3433e j + 0.9025e 2j
lecture #06
November 6, 2016
7 / 23
lecture #06
November 6, 2016
8 / 23
More on LCCDE
FIR Filters
N
X
a(k)y (n k) +
k=1
M
X
y (n) =
b(k)x(n k)
M
X
b(k)x(n k)
b(k)(n k)
H(e j ) =
k=0
M
X
b(1)
6
5 b(0)
h(n) = b(n)
b(5)
b(2)
b(4)
4
3
b(3)
b(k)e jk
k=0
-2
h(n)
h(k)(n k)
k=0
k=0
h(n) =
b(k)x(n k)
k=0
k=0
M
X
M
X
lecture #06
November 6, 2016
9 / 23
-1
10
lecture #06
November 6, 2016
10 / 23
More on LCCDE
Computation Algorithm
When one or more coefficient a(k) are non-zero, there is feed back
and the unit sample response is infinite in length.
y (n) =
Example:
z
N
X
}|
a(k)y (n k) +
k=1
|
y (n) = ay (n 1) + x(n)
H(e j ) =
h(n) = an u(n)
M
X
{
b(k)x(n k)
k=0
{z
Feedback
PM
jk
k=0 b(k)e
P
jk
N
k=1 a(k)e
{z
FeedForward
Numerator Polynomial
Denominator Polynomial
lecture #06
November 6, 2016
11 / 23
lecture #06
November 6, 2016
12 / 23
A Picture
% Initialization
x1 = 0; x2 = 0; x3 = 9; x4 = 0; x5 = 0
read b0, b1, b2, b3. b4, b5
% Loop
x0 = get next input
% Compute output
y = b0*x0 + b1*x1 + b2*x2 + b3*x3 + b4*x4 + b5*x5
% Delay
x5 = x4; x4 = x3; x3 = x2; x2 = x1; x1 = x0
Repeat
lecture #06
November 6, 2016
x(n)
b(1)
b(2)
b(3)
...
b(q)
x(0)
x(1)
x(2)
x(3)
...
x(n q)
y (n)
13 / 23
lecture #06
November 6, 2016
14 / 23
A Picture
% Initialization
x1 = 0; x2 = 0; x3 = 0; x4 = 0; x5 = 0
y1 = 0; y2 = 0; y3 = 0; y4 = 0; y5 = 0
read b0, b1, b2, b3. b4, b5
read a0, a1, a2, a3. a4, a5
% Loop
x0 = get next input
% Compute output
y = b0*x0 + b1*x1 + b2*x2 + b3*x3 + b4*x4 + b5*x5
y = y + a1*y1 + a2*y2 + a3*y3 + a4*y4 + a5*y5
% Delay
x5 = x4; x4 = x3; x3 = x2; x2 = x1; x1 = x0
y5 = y4; y4 = y3; y3 = y2; y2 = y1; y1 = y
Repeat
The author (ITC)
b(0)
lecture #06
November 6, 2016
x(n)
b(0)
b(1)
b(2)
b(3)
...
b(q)
x(0)
x(1)
x(2)
x(3)
...
x(n q)
y (n p)
...
y (3)
y (2)
y (1)
y (0)
a(p)
...
a(3)
a(2)
a(1)
a(0)
y (n)
lecture #06
November 6, 2016
16 / 23
x(n)
h1 (n)
y (n)
h2 (n)
Note that the log magnitude of the cascade is the sum of the log
magnitude of individual systems,
20 log10 |H(e j )| = 20 log10 |H1 (e j )| + 20 log10 |H2 (e j )|
() = 1 () + 2 ()
and a frequency response
H(e j ) = H1 (e j )H2 (e j )
lecture #06
November 6, 2016
17 / 23
h1 (n)
lecture #06
November 6, 2016
18 / 23
+
+
y (n)
x(n)
+
+
w (n)
y (n)
f (n)
h2 (n)
g (n)
W (e j ) = X (e j ) + G (e j )Y (e j )
H(e j ) = H1 (e j ) + H2 (e j )
The author (ITC)
lecture #06
November 6, 2016
19 / 23
lecture #06
Y (e j ) = F (e j )W (e j )
November 6, 2016
20 / 23
Interconnection of System:
Forming New Filters
and
W (e j ) = X (e j ) + G (e j )F (e j )W (e j )
Solving for W (e j )
|Hhp (e j )|
X (e j )
W (e ) =
1 F (e j )G (e j )
j
with
Y (e j ) = F (e j )W (e j ) =
F (e j )X (e j )
1 F (e j )G (e j )
H(e j ) =
F (e j )
1 F (e j )G (e j )
lecture #06
November 6, 2016
21 / 23
lecture #06
lecture #06
November 6, 2016
23 / 23
November 6, 2016
22 / 23